A report of assessment tools for individuals with dysarthria - Altaher, Abeer Muneer; Chu, Shin Ying; Mustaffa Kamal, Rahayu; A Razak, Rogayah (Bentham Science Publishers, 2019)
Introduction: The development of assessment tools for individuals with dysarthria has been reported in many clinical and empirical studies. Methodology: A literature review was based on online resources including Google Scholar, EBSCO, Medline, PubMed, and BIOMED Central articles and journals. Results and Conclusion: In this paper, we summarized the commonly used formal and informal assessment tools and explained the assessment procedure when managing clients with dysarthria. We aimed to share the current practice of speech-language pathologists together with the allied health service providers in the management of patients with dysarthria